Analisis Efisiensi Aktivitas Marketing: Assessment Ocean, Kinerja Pegawai Toyota Surabaya - Wira Kumara Cittopacama, Bima; Hanoum, Syarifa (GEMA EKONOMI, 2023)
This research will examine the relationship between employee personality traits based on the OCEAN assessment that influence job performance during marketing activities. The approach used in this study is a survey with Likert scale. The population and sample were obtained using probability sampling. Based on the research title, "The Influence of Marketing Efficiency on Job Performance." In this case, the variability of variable Y is determined or influenced by X (exogenous), making Y positioned as the endogenous variable. Marketing Activity Efficiency (X1) and OCEAN assessment (X2) are independent variables that exert their influence on the dependent variable, job performance (Y). This research is analyzed using SEM-PLS. The research method includes the Measurement (outer) Model, Structured (inner) Model, and Partial Least Square (PLS). The study aims to test the relationship between personality traits that result in effective employee job performance, in this case, job performance. The findings from this research indicate that Marketing Activity Efficiency has an influence on the OCEAN assessment, specifically Openness, Conscientiousness, Extraversion, and Neuroticism, except for Agreeableness. Marketing Activity Efficiency has an influence on Job Performance. The OCEAN assessment does not have a direct influence on Job Performance